Encyclopedia of birds: The comprehensive illustrated guide by international experts (San Diego, CA, 1998)
The book, with more than 200 magnificent color photographs and 150 carefully researched illustrations, maps, and diagrams, presents an up-to-date and comprehensive survey of the natural history of birds. It provides new conservation information on each order, using symbols to denote the three levels of threat - critically endangered, endangered, and vulnerable
Keywords: birds,zoology; nomenclature